Relationship between the platelet-to-lymphocyte ratio and in-hospital mortality of ischemic stroke patients in the intensive care unit - Liu, Guohua; Zhou, Ya; Ding, Hao; Chen, Lin; Chen, Lan; Yang, Sufang (Frontiers in Aging Neuroscience, 2025)
BackgroundThe relationship between the platelet-to-lymphocyte ratio (PLR) and the prognosis of patients with ischemic stroke was unclear.ObjectiveThis study aimed to explore the correlation between PLR levels and in-hospital mortality in ischemic stroke patients admitted to the intensive care unit (ICU).MethodsA retrospective cohort study was conducted using data from the MIMIC-IV database. Demographic and clinical data of all participants were collected, and the study outcome was in-hospital mortality. Patients were divided into three groups based on the tertiles of PLR: low PLR group (PLR < 0.88), intermediate PLR group (0.88 ≤ PLR < 1.73), and high PLR group (PLR ≥ 1.73). Multivariable-adjusted logistic regression analysis, curve fitting, interaction analysis, and threshold analysis were performed to evaluate the relationship between PLR levels and in-hospital mortality in ischemic stroke patients in the ICU.ResultsA total of 1,002 critically ill patients with ischemic stroke were included, with an average PLR level of 1.88 ± 2.34. The overall in-hospital mortality rate was 12.48%, with mortality rates of 7.38% in the low PLR group, 8.96% in the intermediate PLR group, and 21.15% in the high PLR group. A non-linear J-shaped relationship was found between PLR and in-hospital mortality. The study found that when the PLR value was less than 4.21, there was a positive correlation between PLR and in-hospital mortality. In the subgroup analysis, no statistically significant interactions were found among the subgroups.ConclusionIn the ICU setting, PLR levels were independently associated with in-hospital mortality in critically ill patients with ischemic stroke. When PLR was less than 4.21, this emphasized the importance of close monitoring by ICU physicians.